Direct monitoring of the potassium charge carrier in Prussian blue cathodes using potassium K-edge X-ray absorption spectroscopy - Mayer, Alexander J.; Beynon, Owain T.; Logsdail, Andrew J.; Wijayantha, Upul K. G.; Dann, Sandra E.; Marco, José F.; Elliott, Joshua D.; Aramini, Matteo; Cibin, Giannantonio; Kondrat, Simon A. (Royal Society of Chemistry (RSC), 2023)
Prussian blue is widely utilized as a cathode material in batteries, due to its ability to intercalate alkaline metal ions, including potassium. However, the exact location of potassium or other cations within the complex structure, and how it changes as a function of cycling, is unclear. Herein, we report direct insight into the nature of potassium speciation within Prussian blue during cyclic voltammetry, via operando potassium K-edge X-ray Absorption Near Edge Structure (XANES) analysis. Clear and identifiable spectra are experimentally differentiated for the fully intercalated (fully reduced Fe2+FeII Prussian white), partially intercalated (Prussian blue; Fe3+FeII), and free KNO3(aq) electrolyte. Comparison of the experiment with simulated XANES of theoretical structures indicates that potassium lies within the channels of the Prussian blue structure, but is displaced towards the periphery of the channels by occluded water and/or structural water present resulting from [Fe(CN)6]4− vacancies. The structural composition from the charge carrier perspective was monitored for two samples of differing crystallite size and electrochemical stability. Reproducible potassium XANES spectral sequences were observed for large crystallites (ca. 100 nm) of Prussian blue, in agreement with retention of capacity; in contrast, the capacity of a sample with small crystallites (ca. 14 nm) declined as the potassium became trapped within the partially intercalated Prussian blue. The cause of degradation could be attributed to a significant loss of [Fe(CN)6]–[Fe(NC)6] ordering and the formation of a potassium-free non-conducting ferrihydrite phase. These findings demonstrate the potential of XANES to directly study the nature and evolution of potassium species during an electrochemical process.
Keywords: 40 Engineering; 4016 Materials Engineering; 34 Chemical Sciences; 3406 Physical Chemistry; 3403 Macromolecular and materials chemistry; 4004 Chemical engineering